Political economy of secession: Lessons from the early years of the Irish Free State - Sean Kenny; Eoin McLaughlin (Queen's University Centre for Economic History (QUCEH), 2022)
We apply insights from the political economy of secession to analyse the early years of the Irish Free State (IFS). The IFS was fortuitous in a debt settlement that enabled it to begin its existence debt free, whilst also receiving financial assistance to quell civil unrest. Yet the IFS was unable to continue to provide the welfare spending inherited from the old regime thereby exacerbating inequality. The IFS also maintained a sterling peg, which led to a milder experience of the depression era. Ultimately however, the benefits of independence were not forthcoming in the early years of the IFS.
Keywords: N14; N44; 330; Ireland; economic history; independence; secession